2016
DOI: 10.1002/2016gl069529
|View full text |Cite
|
Sign up to set email alerts
|

Ice‐nucleating particle emissions from photochemically aged diesel and biodiesel exhaust

Abstract: Immersion‐mode ice‐nucleating particle (INP) concentrations from an off‐road diesel engine were measured using a continuous‐flow diffusion chamber at −30°C. Both petrodiesel and biodiesel were utilized, and the exhaust was aged up to 1.5 photochemically equivalent days using an oxidative flow reactor. We found that aged and unaged diesel exhaust of both fuels is not likely to contribute to atmospheric INP concentrations at mixed‐phase cloud conditions. To explore this further, a new limit‐of‐detection paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
73
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(92 citation statements)
references
References 44 publications
15
73
0
1
Order By: Relevance
“…Some held the view that BC is not an efficient ice nucleation active species (Kamphus et al, 2010;Schill et al, 2016), whereas some described BC particles as possible INP (Cozic et al, 2008(Cozic et al, , 2007). …”
Section: Particle Number Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some held the view that BC is not an efficient ice nucleation active species (Kamphus et al, 2010;Schill et al, 2016), whereas some described BC particles as possible INP (Cozic et al, 2008(Cozic et al, , 2007). …”
Section: Particle Number Concentrationsmentioning
confidence: 99%
“…Chou et al (2013) observed that soot particles from diesel engines and wood burning form ice at −40 • C, and unrealistically high relative humidity (RH) was needed for freezing initiation above this temperature. Schill et al (2016) showed that neither fresh nor aged emissions from diesel engines contributed appreciably to atmospheric INP concentrations. However, some studies considered BC-containing particles as possible INP (Cozic et al, 2008;Levin et al, 2016;Cozic et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We follow Schill et al (2016) for correcting sample concentrations for background and for defining confidence intervals for CFDC data, which are represented by error bars in presented plots. Specifically, corrected INP concentrations are the sample concentrations with the interpolated background concentrations subtracted.…”
Section: Colorado State University Cfdcsmentioning
confidence: 99%
“…The former study reported evidence for the incorporation of nitrogen into SOA. OFRs have also been increasingly employed to process emissions of vehicles, biomass burning, and other combustion sources (Table 1) in which NO can often be hundreds of ppm Martinsson et al, 2015;Karjalainen et al, 2016;Link et al, 2016;Schill et al, 2016;Alanen et al, 2017;Simonen et al, 2017). It can be expected that such a high NO input together with very high VOC concentrations would cause a substantial deviation from the good OFR operation conditions identified in Peng et al (2016).…”
Section: Introductionmentioning
confidence: 99%